Long-term variability and trends of extended winter snowfall in Turkey and the role of teleconnection patterns - Baltaci, Hakki; Arslan, Hilal; Akkoyunlu, Bulent Oktay; Gomes, Helber Barros (Wiley, 2020)
In this study, a climatological analysis of daily new snow cover data from 93 meteorological stations (10-2,400 m above sea level) over Turkey during the winter (December-March) period of 1967-2006 is presented. Series of snow cover depth (SCD) (>= 1 cm) and number of snowy days (SDs) were analysed to determine the variability and statistically significant trends in the snow climatology. The results showed an inverse relation between SDs and SCD over the central (CAR) and eastern (EAR) Anatolian regions. While positive trends in SDs were observed in the CAR (77% of all stations), the new SCD decreased in time. On the other hand, the intensity of the daily snowfall over the EAR increased due to decreasing (increasing) SD (SCD) trends in the region, especially between the 500 and 1,000 m layer. It was found that higher SCDs occur in the EAR during winter with positive patterns in the east Atlantic/western Russia. The daily mean sea level pressure composite maps of high SCD (>5 cm) show that strong northeasterly flows enable the penetration of cold polar air to the EAR due to the interaction between the Siberian high-pressure centre over Europe and the low-pressure centre over the Caspian Sea. These results help further understanding of the regional variation of the snowfall pattern in Turkey and its response to global climatic change.
Keywords: snow cover depth (SCD); snowfall; synoptic; teleconnection pattern (TP); Turkey